Cancer mortality predictions for 2025 in Latin America with focus on prostate cancer - Mignozzi, Silvia; Santucci, Claudia; Levi, Fabio; Malvezzi, Matteo; Boffetta, Paolo; Corso, Giovanni; Negri, Eva; La Vecchia, Carlo (European journal of cancer prevention, 2025)
We provided cancer mortality rate estimates for the year 2025 in six Latin American countries (Argentina, Brazil, Chile, Colombia, Cuba, and Mexico), focusing on prostate cancer. We extracted mortality data for all cancers combined and the most common sites from the WHO and population data since 1970 from the United Nations. Estimates for 2025 were computed applying a linear regression to the most recent segment identified through Poisson join-point regression. Avoided deaths number from 1991 to 2025 was estimated by applying the 1990 peak rate to population data. Mortality from all cancers is predicted to be favorable for both sexes in all countries. The lowest total cancer mortality rates are expected in Mexico (67.7/100 000 males; 61.4/100 000 females), while the highest ones in Cuba (136.6/100 000 males; 91.6/100 000 females). Prostate cancer mortality is declining in all countries, although rates remain high in Cuba (25.2/100 000 in 2025). Downward patterns are observed for all age groups in all countries, except the elderly in Cuba and Mexico. Declines in mortality are predicted for colorectal (except for males in Brazil and Cuba, and females in Chile), stomach (except Cuban males), pancreatic (except Argentinian and Cuban males), lung, bladder (except Argentinian females), breast, and ovarian (except Cuba) cancers. Uterine cancer mortality, particularly from cervical cancer, remains highin Argentina (10.2/100 000) and Cuba (10.4/100 000). Except for uterine, stomach, and prostate cancers, cancer mortality rates are still relatively low in Latin America, except Cuba. Controlling tobacco particularly in Cuba, implementing organized cervical cancer screening, and advancing cancer treatment also for prostate cancer remain crucial in all countries considered.